Exploring Vocabulary Learning Strategies in EFL Contexts - Kulsum, Eva Meidi; Fitri , Fajriati Prasetya Cahyaning (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This study tried to analyze the vocabulary learning strategies employed by students. This study employed qualitative descriptive method, involving the distribution of a questionnaire and a semi-structured interview session. This study conducted in one of senior high schools in Bandung, 37 students were selected as participants for this study using a purposive sampling technique. They took part in the questionnaire session while, in the interview session, six students participated. Based on the results obtained, the researcher concluded that there are several strategies used to overcome problems in learning English vocabulary such as determination, social, memory, cognitive and metacognitive strategies. Memory strategies got the highest mean score. It is indicated that the students mostly used this strategy to overcome their problems in learning vocabulary which help them memorize information more effectively. Additionally, this study suggests that providing structured guidance on how to maximize the use of these strategies, such as effective dictionary use, collaborative learning, and utilizing multimedia resources, can further enhance students’ vocabulary acquisition and overall language proficiency.